Case reportLife-saving necklace: collateral circulation from the conus artery to the anterior descending artery - Cam, Fatih; Gungor, Hasan; Unal, Mustafa; Eryilmaz, Ufuk (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We report a case of hyperacute inferior myocardial infarction with life-saving collateral circulation from the conus artery to the left anterior descending artery